Utilization of Information Technology as a Marketing Medium for Agricultural Products at BUMDes Liang Muda STM Hulu Deli Serdang - Efendi, Syahril; Elveny, Marischa; Lubis, Fahrurrozi; Nurahmadi, Fauzan; Jaya, Ivan (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The use of ICT has penetrated into various sectors including in the field of government at the village level, both in village information management as well as village-owned businesses in the form of Badan Usaha Milik Desa (BUMDes). Efforts to run BUMDes in a professional manner have not been carried out properly due to limited human resources in managing BUMDes especially the use of ICT in efforts to increase BUMDes income. This is experienced by BUMDes Liang Muda Village. The method of implementing community service activities consists of problem analysis, website analysis and development, website testing, socialization and training on website use, evaluation and exchange of opinions. The community service team facilitates the creation of village websites and provides assistance to village officials in managing and utilizing it for information dissemination and village promotion. The existence of a village website for the needs of BUMDes can facilitate the dissemination of information in the village so that it can be known by the wider community. Development of a website follow the development of the situation can be carried out in the future to support the BUMDes of Liang Muda Village so that it can be used to help the village community's economy.